Considering health equity when moving from evidence-based guideline recommendations to implementation: a case study from an upper-middle income country on the GRADE approach. Issue 10 (3rd October 2017) - Eslava-Schmalbach, Javier; Mosquera, Paola; Alzate, Juan Pablo; Pottie, Kevin; Welch, Vivian; Akl, Elie A; Jull, Janet; Lang, Eddy; Katikireddi, Srinivasa Vittal; Morton, Rachel; Thabane, Lehana; Shea, Bev; et al.
Abstract: The availability of evidence-based guidelines does not ensure their implementation and use in clinical practice or policy making. Inequities in health have been defined as those inequalities within or between populations that are avoidable, unnecessary and also unjust and unfair. Evidence-based clinical practice and public health guidelines ('guidelines') can be used to target health inequities experienced by disadvantaged populations, although guidelines may unintentionally increase health inequities. For this reason, there is a need for evidence-based clinical practice and public health guidelines to intentionally target health inequities experienced by disadvantaged populations. Current guideline development processes do not include steps for planned implementation of equity-focused guidelines. This article describes nine steps that provide guidance for consideration of equity during guideline implementation. A critical appraisal of the literature followed by a process to build expert consensus was undertaken to define how to include consideration of equity issues during the specific GRADE guideline development process. Using a case study from Colombia we describe nine steps that were used to implement equity-focused GRADE recommendations: (1) identification of disadvantaged groups, (2) quantification of current health inequities, (3) development of equity-sensitive recommendations, (4) identification of key actors for implementation of equity-focused recommendations, (5) identification of barriers and facilitators to the implementation of equity-focused recommendations, (6) development of an equity strategy to be included in the implementation plan, (7) assessment of resources and incentives, (8) development of a communication strategy to support an equity focus and (9) development of monitoring and evaluation strategies. This case study can be used as model for implementing clinical practice guidelines, taking into account equity issues during guideline development and implementation.